Seashells Lost in the Desert: The Syrians Exodus through Sudan to Egypt - Shahla, Waseem Khattab (AUC Knowledge Fountain, 2023)
The Syrian conflict of 2011 resulted in a significant number of Syrians fleeing their homes in search of safety and stability. After the Syrian conflict in 2011, Syrians were allowed access to many countries, including Egypt. However, after the prolonged conflict, access to numerous nations was severely restricted. This thesis examines the challenges faced by Syrian refugees in their journey through Sudan to Egypt, where they hoped to find a better life. The study specifically focuses on the irregular migration route taken by Syrians through Sudan and Egypt, with a focus on the period of 2016 to 2021. This period was marked by increased security measures at the border and restrictions on movement for certain nationalities, making it harder for Syrians to legally enter Egypt. The research employs a combination of engaged ethnography and photo-elicitation to uncover the experiences and challenges faced by Syrian refugees on this route. Additionally, the thesis contextualizes these findings within the broader literature on borders and irregular migration. The researcher's personal experience on this route in 2017 provides a unique perspective that enriches the understanding of the topic. This thesis aims to shed light on the experiences and challenges faced by Syrian refugees and to contribute to the understanding of the socio-economic and political factors that influence forced migration.